Filipina/o/x American Women’s Experiences of and Attitudes Towards Seeking Mental Health Help During College: Findings from a Qualitative Research Study - Almeda, Florence C. (Tufts Archival Research Center, 2022)
Asian Americans are three times less likely to seek mental health services than Whites, despite high rates of suicide and other mental illnesses. Even while evidence suggests that different Asian ethnic subgroups (e.g., Chinese, Japanese, Filipinos, etc.) experience varied mental health concerns, with Filipina/o/x Americans demonstrating poorer mental health outcomes and help-seeking behaviors in comparison to their ethnic counterparts, Asian Americans are often treated as a monolith. The objective of this research study was to explore Filipina/o/x American women’s experience of and attitudes towards seeking mental health help during college. The findings were derived from nineteen in-depth, semi-structured Zoom interviews with Filipina/o/x American undergraduate women from seven different universities in the Northeast. Participants were recruited through the social media pages and personal networks of Filipino collegiate cultural groups at these universities. This study revealed themes related to the role of family in mental health help-seeking and mental health, motivations for participants to adopt a self-therapizing mentality, the importance of alternative spaces (e.g., social networks, cultural and academic communities, faith communities etc.) to process mental health concerns, the inaccessibility of university resources, and the importance of the congruence of multiple identities with mental health professionals for formal mental health help-seeking. This study contributes to our limited understanding of mental health help-seeking among Filipina/o/x American undergraduates, which may inform the creation of culturally sensitive resources, practices, and policies related to supporting this population.; Thesis (B.A.)--Tufts University, 2022.; Submitted to the Dept. of Community Health.; Committee: Shalini Tendulkar and Adolfo Cuevas.